Applying the ADDIE Model to Develop a CAPsMAN-Based Wireless Network Management and Traffic Monitoring System - Septianto, Tri; Nurdiansyah, David; Kusbandono, Hendrik; Paksi, Angger Binuko (NJCA (Nusantara Journal of Computers and Its Applications), 2025)
The advancement of information technology demands wireless networks that are not only stable but also centrally manageable and efficient. In many medium-scale organizations, such as XYZ Company, manual access point management leads to inefficiencies, configuration inconsistencies, and difficulties in monitoring network traffic. To address these issues, this study proposes the development of a wireless network management system based on CAPsMAN (Centralized Access Point Management) with real-time traffic monitoring features, implemented using the Laravel framework. The development process follows a systematic approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), providing a structured methodology for identifying user requirements, designing system architecture, developing the solution, implementing it in a real-world environment, and evaluating system performance. The developed system is integrated with the MikroTik API for direct data retrieval and utilizes a MySQL database for storing traffic history. Implementation results indicate that the system successfully enables centralized management of six access points, simplifies bulk configuration, and provides an intuitive web interface for real-time monitoring of connected devices, network status, and traffic reports. Quantitative monitoring shows peak traffic of 2 MBps (upload) and 21 KBps (download), with data logged every 30 minutes for historical analysis. Prior to implementation, network administrators relied on manual, device-by-device configuration via Winbox without centralized visibilityleading to inconsistent policies and delayed troubleshooting. Post-implementation, all management tasks are unified, and real-time dashboards reduce monitoring latency to near zero. Black-box testing confirms that all system functions operate according to specifications. The application of the ADDIE model proves effective in ensuring the system’s quality, reliability, and sustainability. This research demonstrates that ADDIE can be successfully adapted beyond educational contexts its novel application in network system development ensures a user-centered, traceable, and evaluable engineering process, which is rarely documented in existing literature.